Investigating the Mediating Effect of Ethical Climate on Organizational Justice and Burnout: A Study on Financial Sector - ERDİLEK KARABAY, MELİSA (ELSEVIER SCIENCE BV, 2015)
The literature suggests that ethical climate today is more critical in organizations to sustain positive attitudes and behaviours of employees. Ethical climate is considered to be highly relevant to the financial industry, since it enhances service-providers' contact with customers. This paper examines the interaction between burnout and organizational justice as well as the mediating effect of ethical climate on this relationship. For this purpose, the data (N=543) was collected from the employees working in the financial services, operating in Istanbul. All research hypotheses including mediation were tested by multiple regression analyses to determine whether the conditions of mediation outlined by Baron and Kenny (1986) were addressed. Empirical results indicate that, ethical climate has a partial mediating effect on the relationship between employees' organizational justice perception and burnout. This effect appears particularly for the dimension of distributive justice and depersonalization relation. It can be inferred from the findings that ethical climate plays an important role in governing the relationship between distributive justice and depersonalization. The findings do not show any mediating effect of ethical climate on procedural justice and burnout relation.
Keywords: Organizational Justice; Burnout; Ethical Climate; Mediation; JOB-SATISFACTION; CITIZENSHIP BEHAVIORS; PROCEDURAL JUSTICE; PERFORMANCE; COMMITMENT; HEALTH; PREDICTORS; LEADERSHIP; FAIRNESS; MODELS